2021
DOI: 10.1177/1060028021999647
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pediatric Injectable Medicines Guidelines and Associated Medication Administration Errors: A Human Reliability Analysis

Abstract: Background: In a recent human reliability analysis (HRA) of simulated pediatric resuscitations, ineffective retrieval of preparation and administration instructions from online injectable medicines guidelines was a key factor contributing to medication administration errors (MAEs). Objective: The aim of the present study was to use a specific HRA to understand where intravenous medicines guidelines are vulnerable to misinterpretation, focusing on deviations from expected practice ( discrepancies) that contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Most of the studies concerned administration (n = 8, 50%) 6,31,[33][34][35]40,41,44 or preparation (n = 6, 38%) 32,33,36,39,41,42 phases. Up to 31% (n = 5) 32,34,38,41,44 of the studies utilized research designs that could be interpreted as proactive risk management, while in our earlier systematic review 19 features of prospective risk management could be identified only in 2 studies (18%). 45,46…”
Section: Description Of Studies Exploring Systemic Causes Of IV Mes (...mentioning
confidence: 86%
See 3 more Smart Citations
“…Most of the studies concerned administration (n = 8, 50%) 6,31,[33][34][35]40,41,44 or preparation (n = 6, 38%) 32,33,36,39,41,42 phases. Up to 31% (n = 5) 32,34,38,41,44 of the studies utilized research designs that could be interpreted as proactive risk management, while in our earlier systematic review 19 features of prospective risk management could be identified only in 2 studies (18%). 45,46…”
Section: Description Of Studies Exploring Systemic Causes Of IV Mes (...mentioning
confidence: 86%
“…Our systematic search on Medline (Ovid) found 16 articles describing systemic causes of IV MEs published between June 2016 and October 2021 (Supplementary file 2, http://links.lww.com/ JPS/A612). These studies were conducted in the following 6 countries: United States (n = 6), 6,[30][31][32][33][34] United Kingdom (n = 5), [35][36][37][38][39] France (n = 2), 40,41 Canada (n = 1), 42 South Korea (n = 1), 43 and Spain (n = 1). 44 Most of the studies were carried out in a hospital setting without a specification of a specialty area (n = 7), 6,30,31,34,36,37,43 whereas some were conducted in a pediatric hospital setting (n = 3), 35,39,41 hospital pharmacy (n = 2), 32,42 emergency department (n = 1), 33 intensive care unit (ICU) and hematology sterile unit (n = 1), 40 neonatal intensive care unit (NICU) (n = 1), 44 and a simulated pediatric medical facility (n = 1).…”
Section: Description Of Studies Exploring Systemic Causes Of IV Mes (...mentioning
confidence: 99%
See 2 more Smart Citations
“…information on intravenous medication administration can be a cause of medication errors [23]. Assessing the performance of such guidelines in the hands of 'real' users and subsequently redesigning them to prevent problems might lead to safer medicines administration [24].…”
Section: Areas Of Discussion At the Symposiummentioning
confidence: 99%